Collective identity and wellbeing of Roma minority adolescents in Bulgaria. (27th April 2012) - Dimitrova, Radosveta; Chasiotis, Athanasios; Bender, Michael; van de, Fons
<x xml:space="preserve">Abstract</x> In Europe and particularly in Bulgaria, Roma represent the largest low‐status minority group that is subjected to marked public intolerance and discrimination. This study examined links among Roma (N = 207) and Bulgarian (N = 399) adolescents' ethnic, familial, and religious identities as salient identity aspects for their psychological wellbeing. Results indicated that, as expected, Roma youth reported lower levels of wellbeing than Bulgarian youth. The latter revealed a weaker religious identity than Roma youth, whereas no ethnic group differences emerged regarding Bulgarian or familial identity. Furthermore, we observed that collective identity was higher in older participants of both groups. Finally, a multigroup analysis using structural equation modeling showed that collective identity was a positive predictor of wellbeing for both Roma and Bulgarian adolescents. Findings demonstrated differences in salience as well as structural communalities regarding ways in which collective identity affects wellbeing of youth from two ethnically diverse communities.